Contrasting English and German Grammar : an Introduction to Syntax and Semantics. - Beck, Sigrid (Mouton textbook., 2014)
This book offers an introduction to the derivation of meaning that is accessible and worked out to facilite an understanding of key issues in compositional semantics. The syntactic background offered is generative, the major semantic tool used is set theory. These tools are applied step-by-step to develop essential interface topics and a selection of prominent contrastive topics with material from English and German.